Novel application of robot-guided stereotactic technique on biopsy diagnosis of intracranial lesions - Feng, Yan; Yaming, Wang; Yongzhi, Shan; Penghu, Wei; Hong, Wang; Xiaotong, Fan; Changming, Wang; Sichang, Chen; Guoguang, Zhao (Frontiers in Neurology, 2023)
Introduction This study was performed to examine whether there is a link between the application of three types of robot-guided stereotactic biopsy techniques and the diagnostic rate of intracranial lesion biopsy. Methods The study involved 407 patients who underwent robot-guided stereotactic intracranial lesion biopsy at Xuanwu Hospital of Capital Medical University from January 2019 to December 2021. Age, sex, lesion characteristics, lesion distribution, surgical method, and target path depth were assessed for their impact on the biopsy diagnostic rate. Results The patients’ mean age was 42.1 years (range, 6 months–82 years). All patients underwent robot-assisted stereotactic brain biopsy using one of three different systems: a ROSA robotic system (n=35), the CAS-R-2 (n=65), or the REMEBOT domestic robotic system (n=307). No significant difference was found in the diagnostic rate of positive histopathological findings or the mean time of surgery among the three biopsy modalities. The diagnostic rate was 93.86%. Multiple linear regression analysis showed that age, sex, and biopsy modality did not affect the diagnostic rate n>0.05), whereas enhancing lesions and smaller-volume lesions (≤l cm3) were significantly correlated with the diagnostic rate (p = 0.01). Lesions located in the suprasellar and pineal regions were significantly associated with the negative diagnostic rate (p<0.05). Conclusion The presence of enhancing lesions, lesion location, and lesion volume significantly affected the diagnostic rate of brain biopsy. Age, sex, lesion depth, and biopsy modality did not significantly affect the diagnostic rate. All three procedures had high safety and effectiveness.